Mild solutions of a fractional partial differential equation with noise - Bouteraa, Noureddine; İnç, Mustafa; Akinlar, Mehmet Ali; Bin-Mohsin, Bandar (Wiley, 2021)
This article focuses on studying mild solutions of an original fractional partial differential equation disturbed by multiplicative white noise. We employ techniques of semigroup theory, Hausdorff measure, and Darbo fixed point theorem.
Keywords: Darbo fixed point theorem; fractional PDE; Hausdorff measure; mild solution; multiplicative white noise